Pengaruh Design product, Word Of Mouth Dan Price Terhadap Keputusan Pembelian Sepatu Ventela Di Kota Malang - Harianto, Fajar Dini; Nurhidayah, Nurhidayah; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine the influence of product design, word of mouth, and price on purchasing decisions for Ventela shoes in Malang City. The research method used is quantitative with an explanatory research approach. The research sample of 90 respondents was determined using purposive sampling with the Malhotra formula, namely consumers who have purchased Ventela shoes in Malang City. The data collection technique was carried out through a questionnaire, and the data were analyzed using multiple linear regression with the help of SPSS. The results of the study indicate that simultaneously and partially, the three independent variables, namely product design, word of mouth, and price, have a positive and significant effect on purchasing decisions. Among the three, word of mouth is the most dominant variable influencing purchasing decisions. These findings are expected to be a consideration for business actors in developing more effective marketing strategies, especially in increasing sales of local products such as Ventela shoes. Keywords: Design Product, Word of Mouth, Price, Purchasing Decisions